Combining a non-immersive virtual reality gaming with motor-assisted elliptical exercise increases engagement and physiologic effort in children - Huang, Chun-Kai; Buster, Thad W.; Siu, Ka-Chun; Burnfield, Judith M. (Frontiers in Virtual Reality, 2022)
Virtual reality (VR) gaming is promising in sustaining children’s participation during intensive physical rehabilitation. This study investigated how integration of a custom active serious gaming with a robot-motorized elliptical impacted children’s perception of engagement (Intrinsic Motivation Inventory), physiologic effort (i.e., exercise speed, heart rate, lower extremity muscle activation), and joint kinematics while overriding the motor’s assistance. Compared to Non-VR condition, during the VR-enhanced condition participants’ perceived engagement was 23% greater (p = 0.01), self-selected speed was 10% faster (p = 0.02), heart rate was 7% higher (p = 0.08) and muscle demands increased. Sagittal plane kinematics demonstrated only a small change at the knee. This study demonstrated that VR plays an essential role in promoting greater engagement and physiologic effort in children performing a cyclic locomotor rehabilitation task, without causing any adverse events or substantial disruption in lower extremity joint kinematics. The outcomes of this study provide a foundation for understanding the role of future VR-enhanced interventions and research studies that weigh/balance the need to physiologically challenge a child during training with the value of promoting task-related training to help promote recovery of walking.